First description and bionomic notes for the final-instar larva and pupa of an Oriental dobsonfly species, Neoneuromus sikkimmensis (van der Weele, 1907) (Megaloptera: Corydalidae) - Cao, Chengquan; Tong, Chao; Chen, Shengzhi; Liu, Zhiwei; Xu, Faqiong; Liu, Qian; Liu, Xingyue (Zootaxa, 2016)
Neoneuromus van der Weele, 1909, a member of megalopteran subfamily Corydalinae, is a common and widespread dobsonfly genus of the Oriental Region. The adult taxonomy of Neoneuromus is relatively well-known but the larvae and pupae are undescribed. In this paper we describe the last-instar larva and the pupa of N. sikkimmensis (van der Weele, 1907), representing the first detailed description of any immature stage of Neoneuromus. Information on the bionomics of this species is also reported.